El paisaje lingüístico de la pandemia en la ciudad de Hangzhou - Ma, Yujing (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Research on the urban linguistic landscape has spread around the world with different approaches and from different perspectives. In this paper a brief introduction on the development of linguistic landscape theory and its relationship with Sociolinguistics is presented. The study is located in a Chinese city under the context of the expansion of the coronavirus in order to observe the influence of social current affairs on the urban linguistic landscape. Through the synchronic and diachronic analysis of the signs about the pandemic, the new modalities that obtain the signs, the development and application of new technologies in society, and the measures taken by the Chinese government in the face of the health emergency are revealed. Based on these discoveries, we have reached the conclusion that the linguistic landscape is closely linked to the current social situation and can function as an indicator of it.
Keywords: linguistic landscape; China; coronavirus (covid-19); social reality